Marcas e marcos - uma história de profissão: O Serviço Social na Cidade de São José dos Campos - Silva, Maria Conceição (2007)
The purpose of this research is the review of the Social Service history of São José dos Campos, during specifics histories marks. To review this history, it was established the following axis: history, professional basis and work, comparing these themes with contemporary authors, following the development process of the profession and its historic context. The developed historic marks are based on the decades of 1960 and 1970, decade of 1980; and the decade of 1990, respectively. We can conclude that the Social Service history on the city has, in certain periods, a particular profile, because it appeared in the 60´s, but in the past few years, with a bigger knowledge sharing between the professionals from different locations, search for professional grown and the insertion of the professionals in some organizations, the profession has been developed in national level. With the promulgation of LOAS (Lei Orgânica da Assistência Social), which purpose is the building and improvement of Social Assistance as a public politics, the cities, in order to get money from the federal government, must be aligned with this law. Through the involvement with the LOAS in the city scope, the Social Service work increases and also the insertion of the profession in the society. This history and its knowledge are necessary for the professional formation and it is important during the professional life, because it shows how the Social Service started and was organized in São José dos Campos